The Problems and Perspectives of Property Insurance in Lithuania - Slavickienė, Astrida (Ekonomika, 2000)
There are disclosed the development of insurance activities, discussed the services of insurance companies, analysed the present position and problems of property insurance and presented the suggestions how to solve these problems in the article.